Parent's Education , School-Age Children, and Household Location in American Cities - William Sander; William Testa (European Regional Science Association (ERSA), 2013)
The revealed residential choice of city versus suburbs within large metropolitan areas is examined with particular focus on families with children, especially those with college-educated parents. Probit and bivariate probit estimates are presented for 15 large metropolitan areas in the United States, and for boroughs within New York City. Data are drawn from the Census Bureau?s American Community Survey. It is shown that overall more affluent and educated families with school-age children are less likely to live in many large central cities including Boston, Chicago, New York City, and Philadelphia with a few important exceptions including Charlotte, Seattle, and the borough of Manhattan. We contrast our results with estimates for married and never married respondents without school-age children.
Keywords: 330; cities; households; children; location